Reading Nehemiah: A Structural Analysis of Nehemiah's Covenant Renewal Account and Its Place within the Book of Nehemiah - Arthur, John R.K. (My University, 2012)
Literary approaches to Ezra-Nehemiah studies are becoming more common. However, there is still a lack in the literary study of Ezra-Nehemiah of a structural analysis of Nehemiah's covenant renewal account that respects its particular fit within Nehemiah's story. The aim of this thesis is to explain how the covenant renewal account (commonly held to be Neh 8-10) is integral to the book ofNehemiah (Neh 1-13). Since narrative structural analysis is the study of the semantic structures that preside over a text's creation, this methodology is well suited to discerning whether or not the content found in the covenant renewal account fits within the broader story (and text) of Nehemiah. Accordingly, my structural analysis of the covenant renewal account reveals a deep, underlying structure that shows this account to be an integral piece of the book of Nehemiah.
Keywords: literary appraoches; Ezra-Nehemiah; structural analysis; Arts and Humanities; Religion; Arts and Humanities